Fatherless Generation: Mengungkap Dampak Kehilangan Peran Ayah Terhadap Psikologis Anak dalam Kaca Mata Islam - Rahmadhani, Annisa; Kinantia, Nabila; Aulia Ramadanti, Salsa; Khoerunnisa, Salsa; Fakhruddin, Agus (Darajat: Jurnal Pendidikan Agama Islam, 2024)
This article aims to explore the impact of fatherlessness on children's psychology from anIslamic perspective. This research utilizes a qualitative approach with a descriptive method thatfocuses on the process, principles and procedures to understand problems and find solutions. Data were obtained through interviews with 10 informants, consisting of 9 women and 1 man,who came from various regions and from various regions and agencies, as well as literaturestudies from various relevant sources such as journals, theses, and relevant sources such asjournals, theses, theses, and scientific articles. The results showed that the absence of thefather's role in children's lives, or the phenomenon of fatherlessness, has a significant impact onchildren's psychological of the child. The presence of fathers is very important in creating aharmonious family based on Islamic values based on Islamic values. As a solution, it isimportant to actively contribute from the extended family and the community to supportchildren's psychological development, and the family needs to instill the teachings of andfamilies need to instill the teachings of Islamic teachings that emphasize compassion, and justiceto support mental health in children, while still being based on Islamic principles.